Numerical modeling of condition of the bridge structure based on the results of national surveys - Degtyarev, G.V.; Molotkov, G.S.; Sekisov, A.N.; Datsjo, D.Ð. (International Journal of Engineering and Technology, 2018)
The possibilities of calculating the bearing capacity of hydraulic structures with the use of modern software products are based on the example of a bridge structure in the Krasnodar region. This bridge construction across the river Bezymyannaya is located near the city of Gelendzhik. In the process of inspection some defects were indentified that affect the bearing capacity of the construction: the destruction of the protective layer of concrete by separate segments; corrosion of reinforcemnt in load-bearing elements with loss of cross-section up to 16,6%; corroison of concrete in load-bearing elements of type I and II; cracks in the crossbar with a width of opening up to 0,5 mm, which indicates the overstrain of the structure.
Keywords: Hydrotechnical Constructions; Inspection of Technical Condition; Mathematical Modeling; Numerical Calculation.